Proceedings of the 9th International Conference for Science Educators and Teachers (ICSET 2017) 2017
DOI: 10.2991/icset-17.2017.176
|View full text |Cite
|
Sign up to set email alerts
|

Development of SAVI (Somatic Auditory Visual and Intellectual) Learning Model with Audiovisual to Increase Writing Skill of Elementary Student

Abstract: This research aims to (1) produce SAVI learning model that was effective in improving narrative writing skills of Elementary School students (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
1
0
0
2
Order By: Relevance
“…The first research findings prove that the application of the SAVI learning model is able to make effective learning so that students who have difficulty reading achieve optimal learning outcomes. the findings of this study also prove the findings of Hartati and Sismulyasih (2017) who concluded that the application of SAVI learning models assisted by audio visual was more effective than conventional learning models (24).…”
Section: Discusionsupporting
confidence: 88%
“…The first research findings prove that the application of the SAVI learning model is able to make effective learning so that students who have difficulty reading achieve optimal learning outcomes. the findings of this study also prove the findings of Hartati and Sismulyasih (2017) who concluded that the application of SAVI learning models assisted by audio visual was more effective than conventional learning models (24).…”
Section: Discusionsupporting
confidence: 88%
“…Pembelajaran kretif dan inovatif yang dijelaskan oleh para pakar dalam bidang pendidikan untuk mengatasi permasalahan yang ada dalam pembelajaran matematika, maka dengan pengguna model Somatic, Auditory, Visual, Intellectual (SAVI) dalam pembelajaran matematika, (Umam & Azhar, 2019) menyatakan bahwa pembelajaran matematika sebagai pusat perhatian pada proses instruksional serta melatih siswa untuk berinteraksi dengan lingkungan sekitar agar dapat membangun pengalaman belajarnya sendiri, (Hartati & Sismulyasih, 2017) Model pembelajaran SAVI memiliki empat elemen yaitu belajar dengan bergerak/somatic (S), belajar dengan berbicara dan mendengar/auditory (A), belajar dengan melihat/visualisasi (V), serta belajar menyelesaikan suatu masalah/intellectual (I), (Wijaksana et al, 2018). Model pembelajaran SAVI (Somatic, Auditory, Visual, Intellectualy) merupakan model pembelajaran yang melibatkan emosi, seluruh tubuh, semua indera, dan segenap kedalaman serta keluasan pribadi, menghormati gaya belajar indilipvidu, (Lestari, 2020).…”
Section: Pendahuluanunclassified
“…Model pembelajaran SAVI merupakan model pembelajaran yang menempatkan peserta didik sebagai pusat perhatian pada proses instruksional serta melatih peserta didik untuk berinteraksi dengan lingkungansekitar agar dapat membangun pengalaman belajarnya sendiri (Hartati & S, 2017). Model pembelajaran SAVI memiliki empat elemen yaitu belajar dengan bergerak atau somatic (S), belajar dengan berbicara dan mendengar atau auditory (A), belajar dengan melihat atau visualisasi (V), dan belajar dengan menyelesaikan suatu masalah atau intellectual (I).…”
Section: Model Pembelajaran Saviunclassified